Studying the Role of Mechanical Properties of Cancer Cells in Tumour Detachment, Migration and Secondary Tumour Formation - Higgins, Ghodeejah (Department of Human Biology, 2022)
Tumour cell detachment, migration and invasion, and secondary tumour formation are critical oncogenic processes during cancer metastasis. Although several molecular mechanisms have been reported to facilitate metastasis, it remains elusive how cellular mechanics contribute to these processes. The goal of this thesis was therefore to reveal and understand how cell mechanics contribute to different stages of the metastatic cascade. Directed cell migration was mechanically induced through 2D in vitro scratch assays whereas tumour cell detachment and tumour formation processes were modelled in 3D in vitro collagen matrices using cell spheroid invasion assays or through self-assembly of cells in isolation (i.e., cluster formation) respectively. Metastatic breast cancer cells were used for the tumour detachment and invasion process, while all other processes were studied on melanoma cells of radial growth phase (RGP), vertical growth phase (VGP) and metastatic (MET) stage. To determine intracellular stiffness, particle tracking microrheology was used in 2D and 3D contexts. Protein content of actin and tubulin was quantified with Western blotting and the oncogenic factor TBX3 was assessed with immunofluorescence techniques. The results show that melanoma progression led to decreased stiffness of cells in isolation in 2D, but increased cell stiffness in 3D. For cells in clusters, stiffness was similar across disease stages, however, cluster formation entailed decreased cell stiffness. Cell volume, cytoskeletal content and mitochondrial dynamics were implicated as primary factors that contribute to altered cell stiffness. Further, TBX3 levels in VGP and MET cells in isolation were overexpressed in compliant matrices but were depleted in rigid matrices. For cell clusters, TBX3 levels of MET but not of VGP cells decreased in rigid matrices. Based on the findings on metastatic breast cancer cells, decreased cell stiffness is proposed to drive the detachment of cells from a tumour, and increased cell stiffness facilitates the subsequent migration and invasion. However, the adjustment of the stiffness of invading cells was dependent on matrix rigidity. Taken together, the adjustment of cancer cell properties, both mechanical and molecular, emphasizes the importance of studying cancer cells in their physiologically relevant context. In addition to accounting for changes in dimensionality, it is equally important to consider how cancer cells modify their biomechanical and molecular properties to orchestrate complex processes during different stages of the metastatic cascade.